Development of open platform controller for step-NC compliant CNC system - Chi Adam, Mohd Khairil Anbia (2020)
The Computer Numerical Control (CNC) machines have gone through tremendous upgrades along the years. However, conventional CNC machines could not find its place in the new era of machining under the conventional standard of ISO 6983 due to its limitation in compatibility, language difference and control has caused increase in terms of repurchase cost, reinstallations, reconfigurations and also training of operators. Therefore, this study covers the system which has been designed and developed from outdated and conventional PROLIGHT 1000 Milling CNC machine from Light Intelitek as the lesser cost solution which further discussed in detail based upon upgrades of hardware, architecture, and algorithm design. The hardware of the system was upgraded with the new servo system combined with SSCNET implementation to improve the functionality and efficiency of the new system. Meanwhile the PC-based software internal structure was developed and categorized under six modules which are Menu, Interpreter, 3D Simulation, Machine Motion System, Drill Bit Monitoring and Live Thermal Monitoring. The designed system software is established as UTHM Open CNC Controller (UOCC). It shows that the retrofitted CNC machine has successfully manufactured “Example 1” (STEP-NC) and “13 Drill Hole” (G-Code) files from the UOCC system which indicates that modules in the UOCC system are able to communicate with the CNC machine thus validating the workability of the controller. Moreover, UOCC system has been extended to online environment via Wi-Fi which utilizes Transmission Control Protocol (TCP) Socket in Java which used the PC as server to create socket thus establishing bind connection between UOCC RM mobile phone and the UOCC system, allowing users to remotely monitor the machining process on mobile platform. While the UOCC AR mobile application allow users to view machining setup process through Augmented Reality guide therefore improving the average operating time for experienced users (42.46%) and non-experienced (28.36%). Moreover, the averaged users’ rating shows 93.3% of overall satisfactory from the users which shows that the addition of AR in the system is well received and accepted by the operators of the UOCC.